PTH-259 Sacral nerve stimulation for faecal incontinence – outcomes from a tertiary referral centre. (22nd June 2015) - Quinn, M; Hunt, S; Koh, H; Anderson, J; MacKay, G
Abstract : Introduction: Neuromodulation therapies have gained recognition as effective treatment modalities for faecal incontinence. Sacral Nerve Stimulation (SNS) is the most widely used of these and has favourable short and medium term outcomes. No standard protocols exist for the follow up of these patients. This study aimed to audit our own practice and outcome`s in a tertiary referral centre. Method: Retrospective analysis of prospectively collected data for all patients referred for SNS between January 2009–2013. Data collected included: demographics, test data, implant data, complications, and number of follow-up appointments (out-patient follow up was on a patient request only). Results: 122 patients were referred for consideration of SNS (median age of 57 years (range 32–82)), of which 112 (91.8%) were female. 75 out of 122 patients underwent a test procedure. Of those that did not have a test, the reasons in 19 were unknown, 12 were no longer required after optimising other treatment modalities, 9 are still awaiting a test procedure, 3 patients were treated for prolapse and did not require SNS, 2 declined, and 2 failed to attend. Of the 75 patients who underwent a test procedure, 58 patients had a successful test, 17 failed the test. Of those patient who had a successful test 48 patients have been implanted to date. 1 patient declined implantation after a successful test and 9 patients are awaiting implantation. 47 of 48 patients (88%) have had a good result from implantation and 1 patient experienced treatment failure. The overall complication rate following implantation was 22.9% (11/48). 5 patients had wound infections, with 3 of these patients requiring device removal. 2 of these patients have been re-implanted successfully and 1 awaits re-implantation. 2 patients had post-operative pain, two required lead replacement, 1 had a superficial wound dehiscence, and 1 had a postoperative haematoma not requiring intervention. Median number of follow appointments was 1 (range 0–8). Conclusion: Our success rates for SNS compare favourably with the published literature. Requests for out-patient follow up are low, suggesting patient-led follow up is feasible. Disclosure of interest: None Declared.